The Evaluation of Indonesian National Standardization (SNI) Policy towards Import in Steel Industry - Hartati, Diana Muji (FIA UB, 2017)
The Indonesian government enacted a mandatory national standardization (Standar Nasional Indonesia, SNI) policy for deformed steel bars in 2008. This policy provides the assurance of supplying safe and reliable products for consumers especially in the construction sector. At the same time, the SNI policy can create non-tariff barrier to trade as it raises the cost of compliance. While tariffs are being increasingly eliminated, the government may choose to use standardization as a tool to protect national industries. This paper analyzes the effect of SNI policy as technical barriers on import values using an auxiliary gravity model. This paper applies panel data on steel imports to Indonesia from the eight major exporting countries between 2000 and 2014. The results of the gravity model reveal a negative impact of the SNI policy on the steel import value in Indonesia across all eight main exporters. The findings support the commonly held view that national standards are an impediment to trade.